PREFERENSI ANAK UMUR 8-12 TAHUN TERHADAP PENAMPILAN DOKTER GIGI DI RUMAH SAKIT GIGI DAN MULUT BAITURRAHMAH - Hiranti Harien; Intan Baturo Endo Mahata; Sri Pandu Utami (Universitas Baiturrahmah, 2021)
Introduction: Preference is a greater desire for someone, a choice, or something that is preferred. Preference for appearance is important because appearance or clothing is considered a form of nonverbal communication that expresses belief in abilities, judgment, personal behavior, and professional sense. The patient's level of trust is influenced by their first impression of the dentist and the level of anxiety is influenced by the clothes of the dental care provider. The purpose of this study was to determine the preferences of children aged 8-12 years old towards the appearance of dentists at the Baiturrahmah Dental Hospital. Methods: The type of research was a descriptive survey with the children who visit RSGM Baiturrahmah between August-January 2019 as population. The total number of the respondent was 59 children, obtained by purposive sampling technique. Data analysis was done by using Microsoft Excel. Results: Children in this study liked dentists who wore white coats 83.1%, colored coats with pictures 16.9%, plain personal protective equipment (PPE) 64%, PPE with pictures 36%, scrubs 70%, children-friendly clothing 30% and girls preferred to be treated by female dentists 83%, the boys chose male dentists 83%. Conclusion: The results of this study indicated that children aged 8-12 years at RSGM Baiturrahmah prefer dentists of the same gender, dentists who wear white coats, plain personal protective equipment, and wear scrubs.